2016
DOI: 10.1037/pag0000072
|View full text |Cite
|
Sign up to set email alerts
|

Terminal decline in well-being: The role of social orientation.

Abstract: Well-being development at the end of life is often characterized by steep deteriorations, but individual differences in these terminal declines are substantial and not yet well understood. This study moved beyond the typical consideration of health predictors and explored the role of social orientation and engagement. To do so, we made use of social variables at the behavioral level (self-ratings of social participation) and the motivational level (valuing social and family goals), assessed two to four years b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 113 publications
(157 reference statements)
4
35
1
Order By: Relevance
“…Such a finding is consistent with the idea that religious beliefs, worldviews, and activity may act as a buffer against stress and thereby contribute to well-being (Ellison, 1991). Our finding that social participation and perceived control were both part of the first leaves of the tree and among the top five variable importance (with social participation having 80% of the importance of the top correlate, disability, and perceived control having 53% of the top correlate) ratings underscores earlier reports of the relevance of these variables for outcomes of successful aging (Baltes & Baltes, 1986) and late-life well-being (Gerstorf et al, 2014;Gerstorf et al, 2016;Wallace et al, 2002).…”
Section: Multi-indicator Constellations Of Physical Health and Psychosupporting
confidence: 74%
“…Such a finding is consistent with the idea that religious beliefs, worldviews, and activity may act as a buffer against stress and thereby contribute to well-being (Ellison, 1991). Our finding that social participation and perceived control were both part of the first leaves of the tree and among the top five variable importance (with social participation having 80% of the importance of the top correlate, disability, and perceived control having 53% of the top correlate) ratings underscores earlier reports of the relevance of these variables for outcomes of successful aging (Baltes & Baltes, 1986) and late-life well-being (Gerstorf et al, 2014;Gerstorf et al, 2016;Wallace et al, 2002).…”
Section: Multi-indicator Constellations Of Physical Health and Psychosupporting
confidence: 74%
“…Moreover, volunteering is only one aspect of social participation. For example, informal social activity (with friends and relatives) and social orientation are known to be relevant for well-being and health, particularly late in life (Gerstorf et al, 2016). It would thus be instrumental to further pinpoint how particular aspects of social orientation may result in reduced health sensitivity, especially because our results suggest that health sensitivity is predictive of mortality hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Also, having an active orientation towards social contacts may help individuals to maintain high levels of well-being by being socially active. Social orientation is associated both with late-life well-being (Gerstorf et al, 2016; Windsor, Gerstorf, & Luszcz, 2015) and reduced mortality risks (Antonucci, 2001; House, Landis, & Umberson, 1988). For example, Barger (2013) reported that social integration predicted lower risk for all-cause mortality over five years in a representative US sample.…”
Section: The Role Of Physical Health Perceived Control and Social Omentioning
confidence: 99%